Role Of Nutritious Diet During Pregnancy W.S.R. To Garbhini Pricharya: A Review - Sharma, Kiran; Devi, Durgawati (International Research Journal of Ayurveda & Yoga, 2024)
Women have special dietary needs during each stage of pregnancy. During pregnancy the mother’s nutrition bears a great impact on the foetus growth and its future. The primary aim of antenatal care is to achieve at the end of pregnancy a healthy mother and a healthy baby. A combination of aahara (diet), vihara (regimen) and aushadha (medication) have been given great significance in Ayurveda in antenatal care called as Garbhini Pricharya. Ayurveda advises a specific diet regimen throughout the pregnancy. Milk and Ghee stand out as the most common in the pregnant diet that Ayurveda advises. The idea of this is to provide optimum amount of protein and fat to the body. In addition, it provides right amount of calcium and vitamins for the pregnant mother helping in sustaining a comfortable lactation. In this review article a designed protocol of the month wise diet advised by various ancient Ayurvedic physician, which can be modified according to present era has been presented. During 1st trimester of pregnancy use of cold and sweet liquid and milk will prevent dehydration and supply required nourishment. Fourth month onward muscular tissue of foetus grows sufficiently requiring more protein which is supplied by use of meat soup. Use of gokshur a good diuretic in 6th month will prevent retention of water as well as its complication. Most women experience constipation in late pregnancy due to pressure of gravid uterus over the bowels and effect of progesterone. Use of enema in 8th month will relieve this constipation. The pregnancy diet should be light, nutritious, easily digestible and rich proteins, mineral and vitamins. The instruction about diet should be reasonable and realistic to individual women. The main aim of this study to generate a complete module for garbhini diet.